Evaluacion de la variabilidad de resultados por la toma de datos en campo utilizados en metodos y modelos para el mantenimiento del pavimento. - Gabriela Michelle, Castillo Barrionuevo (2020)
There are several investigations that make comparisons between pavement condition assessment methods and the application of deterioration prediction models, without taking into account accurate data collection and the influence this may have on their results. It is for this reason that a research focused on evaluating the variability of results by taking data in the field was proposed. Variability is measured with the help of Pearson's coefficient of variation. To meet this objective, a field evaluation tool was developed and applied to a representative sample of 20 people with knowledge of road maintenance on 3 flexible pavement roads subject to different maintenance conditions in the urban area of Riobamba in order to collect data to evaluate the variability of results. Using SPSS software for the processing and subsequent interpretation of data it was found that there is variability of results in the method, but not in the prediction model. The factor that influences the existence of variability in the evaluation method is the number of faults (19 faults) and through a hierarchical analytical process (AHP) using criteria such as the frequency with which each fault is found, the degree of affectation and the percentage of each fault found, was reduced to 9 faults to be evaluated specifically in the urban area of Riobamba.